KEPEMILIKAN RELATIF (AL-MILKIYAH AL-MUQAYYADAH) PRIVAT DAN PUBLIK DALAM EKONOMI ISLAM - Sarmiana Batubara (JURIS (Jurnal Ilmiah Syariah), 2017)
This paper discusses how ownership in the Islamic economy, especially about relative ownership (almilkiyah al-muqayyadah) from the perspectives of the Qur'an and hadith. This is a library research. The conclusions of this discussion are: 1) The concept of ownership is really regulated in the Qur'an and Hadith where many verses of Al-qur'an and Hadith that discuss about the relative ownership of both private and public ownership. 2) The possessions of human beings are not his essential property. Human ownership is only a substitute and a representative of God over the earth. It is an obligation for humans to infaon their possessions in order to fulfill God's right to him, as well as the obligation of a person to provide for his family and to spend another's fortune if permitted. Islam recognizes the existence of individual ownership, but it is not an absolute possession, that is ownership which is limited by certain rules. Islam has established the permissibility of each individual to own property in private. 3) Islam not only recognizes individual ownership that is essentially concerned only with private rights, but also recognizes ownership in general so that it can be exploited by the people, such as water, grass and fire.